Knowledge level of nurses employed in orthopedic units on osteoporosis disease - M Solimanha; K Asadi; S Shabani; AR Mirblock; A Karimi; E Kazemnezhad lili (Guilan University of Medical Sciences, 2014)
Introduction : Osteoporosis is a common problem of musculoskeletal system. Awareness of people about the etiology and risk factors could play an important role in taking care of themselves and others for prevention of osteoporosis. Objective : This study was performed to determine Knowledge level of nurses employed in orthopedic units on osteoporosis disease Materials and Methods : This was a cross-sectional study conducted on 130 orthopedic nurses employed in hospitals of Poursina, Emam Khomeini, Akhtar and Shariati who entered the study by consensus during 2011. Data collection tools included a researcher-made questionnaire consisting of personal and social information and awareness level on Osteoporosis in four domains: prevention, risk factors, nutrition and treatment. Data were analyzed using Frequency, Mean, Standard Deviation, T-test and ANOVA. Results: The average score of awarenesswas14.57±2.81 (out of 20 scores) . Level of awareness was average in participants. In studying the relationship between the awareness level of all mentioned factors of Osteoporosis and also obtained total score of awareness and demographic characteristics (age, gender, work history, education level), a significant relationship was found between age and level of awareness of treatment (P=0.020), education and level of awareness of prevention (P=0.043), risk factor (P=0.031) and total awareness score (P=0.010). Conclusion : In most cases knowledge level of nurses were low. Considering their role in health of society, they should have higher scientific abilities, therefore their knowledge level should be increased regarding osteoporosis and demands exact planning.